ExcLAMation marks in a pelvic lymph node - Yuki Muroyama; Chihiro Inoue; Fumiyoshi Fujishima; Shogo Shigeta; Junko Hasegawa‐Minato; Muneaki Shimada; Takashi Suzuki (Clinical Case Reports, 2023)
Key Clinical Message Extrapulmonary lymphangioleiomyomatosis (LAM) can present as incidental nodal LAM in gynecological surgery specimens, that warrants systemic investigation and follow‐up of concurrent and subsequent development of pulmonary and extrapulmonary LAM.